2016
DOI: 10.1038/srep38609
|View full text |Cite
|
Sign up to set email alerts
|

New principle for measuring arterial blood oxygenation, enabling motion-robust remote monitoring

Abstract: Finger-oximeters are ubiquitously used for patient monitoring in hospitals worldwide. Recently, remote measurement of arterial blood oxygenation (SpO2) with a camera has been demonstrated. Both contact and remote measurements, however, require the subject to remain static for accurate SpO2 values. This is due to the use of the common ratio-of-ratios measurement principle that measures the relative pulsatility at different wavelengths. Since the amplitudes are small, they are easily corrupted by motion-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
75
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 35 publications
(57 reference statements)
3
75
0
2
Order By: Relevance
“…We demonstrate that, based on a dataset with only small variations in SpO 2 , an accurate calibration model can be determined which outperforms a calibration model based on modelling of the PPG spectrum. Furthermore, we show that the error only slightly increases using solely near-infrared (NIR) wavelengths when compared to the typical combination of visible red and NIR wavelengths, which confirms our earlier observations [8] and widens the scope for camera-based pulse-oximetry, e.g., for sleep or continuous 24/7 monitoring where patients are monitored in full darkness.…”
Section: Introductionsupporting
confidence: 85%
See 4 more Smart Citations
“…We demonstrate that, based on a dataset with only small variations in SpO 2 , an accurate calibration model can be determined which outperforms a calibration model based on modelling of the PPG spectrum. Furthermore, we show that the error only slightly increases using solely near-infrared (NIR) wavelengths when compared to the typical combination of visible red and NIR wavelengths, which confirms our earlier observations [8] and widens the scope for camera-based pulse-oximetry, e.g., for sleep or continuous 24/7 monitoring where patients are monitored in full darkness.…”
Section: Introductionsupporting
confidence: 85%
“…In this paper, we present an empirical, data-driven approach to estimate a calibration model for the indirect APBV method which can be applied to an arbitrary number and selection of wavelengths. This is relevant, as in our earlier paper [8], we showed that adding a third wavelength improves the robustness of the measurement. We demonstrate that, based on a dataset with only small variations in SpO 2 , an accurate calibration model can be determined which outperforms a calibration model based on modelling of the PPG spectrum.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations